Sensitization pattern of crustacean‐allergic individuals can indicate allergy to molluscs. Issue 11 (11th August 2015) - Vidal, C.; Bartolomé, B.; Rodríguez, V.; Armisén, M.; Linneberg, A.; González‐Quintela, A.
Abstract This study investigated the sensitization pattern of crustacean‐allergic patients according to tolerance to molluscs. Thirty‐one patients with anaphylaxis to crustaceans (14 with mollusc allergy and 17 with mollusc tolerance) were studied using skin prick tests (SPTs), specific IgEs (sIgEs) and SDS‐PAGE immunoblotting. IgE‐reactive shrimp proteins were identified by proteomic analyses. Patients with mollusc allergy presented more frequently SPTs positive to molluscs and higher sIgE titres in response to both molluscs and crustaceans. Shrimp‐sIgE and rPen a1‐sIgE values of 1.57 kUA/l and 4.38 kUA/l, respectively, showed positive likelihood ratios of 4.3 and 10.9 for the identification of mollusc allergy. Patients with mollusc allergy reacted more frequently to tropomyosin in immunoblots than did patients without it (93% vs 35%, respectively, P = 0.004). Reactivity to proteins other than tropomyosin (n = 14) was not different between the two groups. Among patients with crustacean anaphylaxis, patients with mollusc allergy and mollusc tolerance show a different pattern of sensitization, something that may help identify them.